Pyruvate: Ferredoxin oxidoreductase is involved in IgA-related microbiota dysbiosis and intestinal inflammation - Wang, Kairuo; Guo, Yixuan; Liu, Yuanyuan; Cui, Xiao; Gu, Xiang; Li, Lixiang; Li, Yanqing; Li, Ming (Frontiers in Immunology, 2022)
Introduction Inflammatory bowel diseases (IBDs) are associated with both immune abnormalities and dysbiosis, characterized by a loss of Faecalibacterium prausnitzii (F. prausnitzii). However, the reason for F. prausnitzii deficiency remains unclear. Methods 16S rDNA sequencing and IgA enzyme-linked immunosorbent assay (ELISA) were applied to identify bacterial community and IgA changes in ulcerative colitis (UC) patients. Forced immunization with F. prausnitzii in rabbits was conducted. To screen for potential IgA-reactive proteins in F. prausnitzii lysates, we performed western blotting and mass spectrometry analyses. Pyruvate: ferredoxin oxidoreductase (PFOR) was cloned and purified, then the immunoreactivity of PFOR was verified in peripheral blood mononuclear cells (PBMCs) through PCR, ELISpot assay and single-cell sequencing (scRNA-seq). Finally, the UC fecal dysbiosis was re-analyzed in the context of the phylogenetic tree of PFOR. Results F. prausnitzii was underrepresented in UC patients with elevated F. prausnitzii-reactive IgA in the fecal supernatant. Forced immunization with F. prausnitzii in rabbits led to high interferon-γ (IFN-γ) transcription in the colon, along with beta diversity disturbance and intestinal inflammation. PFOR was identified as an IgA-binding antigen of F. prausnitzii and the immunoreactivity was validated in PBMCs, which showed elevated expression of inflammatory cytokines. The scRNA-seq revealed enhanced signals in both T regulatory cells (Tregs) and monocytes after PFOR incubation. Furthermore, phylogenetic analysis revealed that PFOR was a common but conserved protein among the gut bacteria. Discussion Our results collectively suggest that PFOR is a bioactive protein in the immune system and may contribute to host-microbial crosstalk. Conserved but bioactive microbial proteins, such as PFOR, warrant more attention in future host-microbial interaction studies.